Carbon dioxide and nitrous oxide emissions from a typical sugarcane soil in the Cauca River Valley, Colombia - Valencia Molina, Manuel C.; Chalco Vera, Jorge; Loaiza, Sandra; Trujillo, Catalina; Munera, Bryan; Castro Franco, Mauricio; Silva Parra, Amanda; Chirinda, Ngonidzashe; Munoz Arboleda, Fernando (Springer, 2024)
Abstract Sugarcane is an important crop for tropical countries and to accurately inventory its greenhouse gas (GHG) emissions baseline measurements are needed. In Colombia, sugarcane is one of the most important crops in terms of cultivated area and, paradoxically, scientific information reporting GHG emissions based on field measurements is almost nonexistent. The objective of this work was to quantify the direct emissions of carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) in the sugarcane-soil system of the Cauca river valley, Colombia. For this purpose, a field experiment was established in a typic haplustert soil cropped with sugarcane. The effects of nitrogen (N) fertilization and sampling site on its GHG emissions were tested using the closed static chamber method over a period of 211 days. The main cumulative emissions were 765.14 ± 34.1 g CO 2 –C m −2 and 125.4 ± 22.6 mg N 2 O–N m −2 . Overall, GHG emissions were modified by N fertilization, the sampling site, and their interaction. Nitrogen fertilization with urea increased mean and cumulative CO 2 and N 2 O emissions, especially at the row sampling site. This paper highlights the importance of considering these factors when the quantification of GHGs or a reduction of their associated uncertainties are required. This work reportss the first GHG emissions data for a typical sugarcane agroecosystem in Colombia.